2010
DOI: 10.1177/1947601909360812
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nuclear Localization of a Long Interspersed Nuclear Element-1 Protein in Breast Tumors with Poor Prognostic Outcomes

Abstract: Within healthy human somatic cells, retrotransposition by long interspersed nuclear element-1 (also known as LINE-1 or L1) is thought to be held in check by a variety of mechanisms, including DNA methylation and RNAi. The expression of L1-ORF1 protein, which is rarely found in normal tissue, was assayed using antibodies with a variety of clinical cancer specimens and cancer cell lines. L1-ORF1p expression was detected in nearly all breast tumors that the authors examined, and the protein was also present in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 44 publications
10
70
0
Order By: Relevance
“…14 There are approximately 500,000 copies of LINE-1 across the human genome, occurring as hypermethylated sequences under physiologically normal conditions. Percent LINE-1 methylation has been used as a surrogate for genome-wide methylation 15,16 and has been studied as a potential biomarker for breast cancer risk. [17][18][19] Genome-wide DNA methylation (e.g., measured in repetitive sequences including, Alu, Sat2, and LINE-1) in white blood cells (WBCs) has been shown to be associated with age, gender, race, alcohol exposure, and family history of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…14 There are approximately 500,000 copies of LINE-1 across the human genome, occurring as hypermethylated sequences under physiologically normal conditions. Percent LINE-1 methylation has been used as a surrogate for genome-wide methylation 15,16 and has been studied as a potential biomarker for breast cancer risk. [17][18][19] Genome-wide DNA methylation (e.g., measured in repetitive sequences including, Alu, Sat2, and LINE-1) in white blood cells (WBCs) has been shown to be associated with age, gender, race, alcohol exposure, and family history of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, it was reported that LINE-1 ORF-1p was also likely to play its own role in tumor development. LINE-1 ORF-1p was highly expressed in a variety of tumor tissues associated with poor prognosis (Cho et al, 2007;Harris et al, 2010), but the specific molecular mechanism of its role was still not entirely clear. The results of this study suggested that LINE-1 ORF-1p is not only the main adjustment factor of LINE-1 ORF-2p, but also plays specific roles itself.…”
Section: Discussionmentioning
confidence: 99%
“…Basic research has also shown that ETS-1 is involved in anti-apoptosis, proliferation, accelerated invasion, and metastasis regulation through promoting the transcription of downstream genes associated with invasion and Cyclin D expression (Cho et al, 2007;Peng et al, 2009). The activity of transcription factors is modulated by a large number of co-regulatory factors, including SRC-1, SRC-2, SMRT, and NcoR, among others (Harris et al, 2010). It is valuable to identify novel co-regulatory factors for the various activities of ETS-1.…”
Section: Introductionmentioning
confidence: 99%
“…Retrotransposon overdose is another potential scenario in malignancy and could result in increased insertional mutagenesis, toxicity, or other oncogenic effects. Indeed, the overexpression of L1 ORF1p was observed in certain tumors (Bratthauer and Fanning 1992;Asch et al 1996;Su et al 2007;Harris et al 2010), and RNAi-mediated silencing of L1s resulted in reduced proliferation and differentiation of tumorigenic cell lines (Oricchio et al 2007). In addition, overexpression of Alu elements may exert disease through RNA toxicity (Kaneko et al 2011).…”
mentioning
confidence: 99%